Clinical perspectives for the practicing neurosurgeon on integrative multiomic analyses of aggressive meningiomas - Shree S. Pari; Megan M. J. Bauman; Sangami Pugazenthi; Asad M. Lak; Harsh Shah; Zachary Moynihan; Ziyan Zhang; Albert H. Kim; Wenya Linda Bi; Bhuvic Patel (Neurosurgical Focus, 2026)
Meningiomas are the most common primary intracranial tumor and demonstrate marked heterogeneity in clinical behavior, ranging from indolent lesions cured by surgery to tumors characterized by early recurrence, treatment resistance, and neurological morbidity. The current WHO classification system, based predominantly on histopathological features with limited incorporation of molecular alterations, remains the global standard for grading. However, accumulating evidence indicates that WHO grade alone incompletely captures biological aggressiveness and risk of progression. Over the past decade, integrative molecular investigations, including genomic, transcriptomic, epigenetic, and copy number–based analyses, have generated multiple independent classification schemas that more accurately stratify recurrence risk and clinical outcomes. Although these systems are not yet standardized or incorporated into formal WHO criteria, they consistently identify biologically distinct meningioma subgroups with clinically meaningful prognostic implications. This review synthesizes the current molecular classification landscape with a specific focus on its relevance to neurosurgical practice. We summarize key findings from single-omic and integrative studies, compare emerging schemas with traditional histopathological grading, and discuss how molecular risk stratification may influence surgical decision-making, surveillance strategies, and adjuvant therapy considerations. As molecular diagnostics become increasingly accessible, neurosurgeons will be confronted with this information in routine practice. A practical understanding of the strengths, limitations, and clinical implications for molecular diagnostics will be essential for optimizing the management of patients with aggressive meningiomas.